2018
DOI: 10.3389/fendo.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Genome-Wide Association Analyses of Serum Uric Acid in Middle and Old-Aged Chinese Twins

Abstract: Serum uric acid (SUA), as the end product of purine metabolism, has proven emerging roles in human disorders. Here based on a sample of 379 middle and old-aged Chinese twin pairs, we aimed to explore the magnitude of genetic impact on SUA variation by performing sex-limitation twin modeling analyses and further detect specific genetic variants related to SUA by conducting a genome-wide association study. Monozygotic (MZ) twin correlation for SUA level (rMZ = 0.56) was larger than for dizygotic (DZ) twin correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…Genetic heritability of serum urate varies between 30% and 60% in diverse populations [6][7][8][9][10][11] . Candidate gene and early genome-wide associations studies (GWAS) have identified three genes as major determinants of urate levels: SLC2A9, ABCG2, and SLC22A12 7,[12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic heritability of serum urate varies between 30% and 60% in diverse populations [6][7][8][9][10][11] . Candidate gene and early genome-wide associations studies (GWAS) have identified three genes as major determinants of urate levels: SLC2A9, ABCG2, and SLC22A12 7,[12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk factors for hyperuricemia have not been fully determined, recent studies have shown that apart from genetic variations [ 26 ], several lifestyle or dietary factors have been associated with hyperuricemia. As uric acid is an ultimate product of purine metabolism, hyperuricemia is related to the intake of purine-rich food.…”
Section: Introductionmentioning
confidence: 99%
“…Twin samples will have a higher power in genetic study, especially in human complex diseases ( 21 ). Here based on 382 Chinese twin pairs, we explored the genetic effect on TC, HDL-C, LDL-C variation and further searched for genetic susceptibility loci for these traits using GWAS ( 22 ).…”
Section: Introductionmentioning
confidence: 99%